Effects of astaxanthin‐rich dried cell powder from Paracoccus carotinifaciens on carotenoid composition and lipid peroxidation in skeletal muscle of broiler chickens under thermo‐neutral or realistic high temperature conditions. (16th December 2018) - Inoue, Hiroki; Shimamoto, Saki; Takahashi, Hironori; Kawashima, Yuki; Wataru, Sato; Ijiri, Daichi; Ohtsuka, Akira
Abstract: Thirty‐two 15‐day old broiler chicks (Chunky strain ROSS 308) were randomly divided into four treatments in a 2 × 2 factorial design. The main factors were diet (basal diet or basal diet supplemented with 0.15% astaxanthin‐rich dried cell powder (Panaferd‐P [astaxanthin 30 ppm]) and ambient temperature (thermo‐neutral [25 ± 1°C] or high [35 ± 1°C for 6 hr]). Dietary supplementation with Panaferd‐P did not affect growth performance, though high ambient temperature decreased feed intake and the weight of breast tender muscle, liver, and heart. High ambient temperature also decreased redness in both breast and leg muscles of chickens, while Panaferd‐P increased redness and yellowness of breast and leg muscles of chickens. Panaferd‐P increased Paracoccus carotinifaciens ‐derived pigments (i.e., adonixanthin, astaxanthin, adonirubin, and cantaxanthin) as well as corn‐derived pigments such as zeaxanthin and lutein in breast and leg muscles. High ambient temperature increased the malondialdehyde (MDA) concentration in breast muscle, while Panaferd‐P decreased the MDA concentration in breast muscle under both temperature conditions. Our results suggest that dietary supplementation with Panaferd‐P increases muscle carotenoid content, the redness and yellowness of meat and decreases the muscle MDA concentration in broiler chickens kept under thermo‐neutral or high ambient temperature conditions.